2017
DOI: 10.1155/2017/2565703
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Optical and Electrical Characteristics by Laterally Stretching DNAs on CVD-Grown Monolayers of MoS2

Abstract: Monolayer MoS2 (1L-MoS2) is an ideal platform to examine and manipulate two dimensionally confined exciton complexes, which provides a large variety of modulating the optical and electrical properties of 1L-MoS2. Extensive studies of external doping and hybridization exhibit the possibilities of engineering the optical and electrical performance of 1L-MoS2. However, biomodifications of 1L-MoS2 and the characterization and applications of such hybrid structures are rarely reported. In this paper, we present a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…For example, chemical doping, bio functionalization, applying strain, hybridization, etc., to 2D materials or the formation of 2D heterostructures are most widely used techniques at the present time. [118][119][120][121][122][123] However, among these various techniques, the formation of 2D heterostructures can be considered as one of the most effective methods. 2D heterostructures are particularly found to be effective for tailoring or increasing the physical properties of target materials.…”
Section: First Generation 2d Heterostructurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, chemical doping, bio functionalization, applying strain, hybridization, etc., to 2D materials or the formation of 2D heterostructures are most widely used techniques at the present time. [118][119][120][121][122][123] However, among these various techniques, the formation of 2D heterostructures can be considered as one of the most effective methods. 2D heterostructures are particularly found to be effective for tailoring or increasing the physical properties of target materials.…”
Section: First Generation 2d Heterostructurementioning
confidence: 99%
“…© 2020 Wiley-VCH GmbH pumping from the MXene's side. [122,124] Moreover, such excitonic populations can be still much enhanced with proper selection of MXene and 2D organic species following type II band alignment due to enhanced many-body interactions in such 2D heterostructures. Figure 11a shows the schematic illustration of an exciton-polariton micro cavity device, consisting of a particular 2D MXene/organic heterostructure coated with Al 2 O 3 placed in between SiO 2 /TiO 2 distributed Bragg Reflector mirrors.…”
Section: (18 Of 25)mentioning
confidence: 99%
“…Specifically, 2D semiconducting materials exhibit unique and exciting electronic, optical, mechanical, and optoelectronic properties, [1][2][3][4]8,9,12] and are being explored in many scientific applications involving optoelectronic design, optomechanical design etc. [5,6,11] The large surface-to-volume ratio of 2D materials allows tuning of their inherent properties using a variety of techniques including strain engineering, [14,15] dielectric screening, [16,17] defect engineering, [18,19] chemical doping, [20,21] electrostatic gating, [22,23] hybridization with nanostructures [24,25] and the formation of heterostructures, multi-heterostructures and super lattices. [26][27][28][29] This Review will specifically focus on 2D heterostructures that consist of two different atomic building blocks through weak van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The PL and Raman measurement results of 1L-MoS 2 before and after the plasma treatment were the same, which indicated that there was no physical damage. The O 2 -plasma treatment 38 was performed under an operating pressure of 1.3 × 10 −3 Pa, RF power of 50 W, and oxygen gas flow of 5 sccm for 5 s. The CuPc NPs were dispersed on 1L-MoS 2 by spin coating.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%